Hannah Arendt e o problema da normatividade - Hugo Araújo Prado (2015)
The aim of the dissertation was to analyze the problem of normativity in the context of Hannah Arendts thought. The problem in discussion extracts its sense of the questions: what is the meaning of politics? and what may offer a guide for the political action for governorsand the governed?. I sought first to offer the boundaries of the problem. Therefore I accomplished a debate between her thought and Leo Strausss on the problem of the human nature in politics and the problem of the methodology of political philosophy/theory, pointingout the differences of their positions. I extracted of this debate the conclusion that the normativity can only be conceived to Arendt in a weak sense. After this I tried to explore three interpretive strands on the problem. The first points out for the insufficiency of Arendtstheory to think the normativity (Habermas, 1977; Benhabib, 2000). Two others positions point to the possibility to understand normativity through concepts developed by Arendt. One position would be referred to the concept of natality (Birmingham, 2006), while other positionwould be referred to the concept of plurality (Canovan, 1992). Finally, in the light of the interpretative strands, I sought to evaluate the plausibility of the hypothesis that thenormativity means the preservation of freedom.